Drugs for discoid lupus erythematosus - Jessop, Sue; Whitelaw, David A.; Grainge, Matthew J.; Jayasekera, Prativa (Wiley, 2017)
BACKGROUND: Discoid lupus erythematosus (DLE) is a chronic form of cutaneous lupus, which can cause scarring. Many drugs have been used to treat this disease and some (such as thalidomide, cyclophosphamide and azathioprine) are potentially toxic. This is an update of a Cochrane Review first published in 2000, and previously updated in 2009. We wanted to update the review to assess whether any new information was available to treat DLE, as we were still unsure of the effectiveness of available drugs and how to select the most appropriate treatment for an individual with DLE.